The Potential of Lime Juice in Reducing Fe Levels and Improving the Quality of Clove Leaf Oil Using Complexometry and Testing Its Antioxidant Activity Using DPPH (1,1-Diphenyl-2-picrylhydrazil) - Teti Wulan Wulandari; Susy Yunita Prabawati (Biology, Medicine, & Natural Product Chemistry, 2025)
Clove leaf oil from Samigaluh, Kulon Progo has high Fe content and low eugenol content due to an ineffective distillation process. This study aims to analyze the ability of lime juice as a purifying agent in reducing iron content through complexometry, varying the concentration of lime juice (2%, 3%, and 4%) and stirring time (30, 60, and 90 minutes) on 50 mL of clove leaf oil mixed with 50 mL of lime juice. Eugenol isolation was performed using KOH-H2SO4 extraction. Testing was also conducted on eugenol content, acid number, refractive index, specific gravity, and antioxidant activity using DPPH. Sample testing was performed using AAS, GC, and UV-Vis spectrophotometry. Optimal conditions were obtained at a lime juice concentration of 4% with 60 minutes of stirring, which successfully reduced Fe content from 17.6 to 1.7 mg/kg, increased eugenol content from 75.908% to 78.730% at a lime juice concentration of 3% and 90 minutes of stirring, reducing the acid number from 1.82 to 0.94 mg NaOH/g, increasing the refractive index from 1.331 to 1.529, and increasing the specific gravity from 1.020 to 1.036. Further redistillation with KOH and H2SO4 increased the purity of eugenol to 96.476% with strong antioxidant activity (IC50 57.45 ppm).